Kuat Tekan Dan Kuat Geser Tanah Lempung Lunak Dengan Penambahan Limbah Karbit Dan Fly Ash - Syamsyukur Syamsyukur; Paulus Lebang; Suryani Syahrir (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
Expansive clay soil is a soil that has poor soil properties in most parts of Indonesia. It has soil properties that easily absorb large amounts of water so that it has sensitivity to the influence of water and is very easy to expand. construction by adding stability material aims to increase the bearing capacity of the soil. using waste carbide and fly ash as a stabilizing agent. This study used 12% addition of waste carbide and variations of fly ash 2.5%, 5%, 7.5%, 10% and 12.5% of the dry weight of the soil. From the results of this study, it was found that the compressive strength and shear strength test values with the addition of 7.5% fly ash + 12% carbide waste experienced a maximum increase, so that the maximum free compressive strength qu value was 1.145 kg/cm2 and the direct shear strength got the maximum shear strength value of 0.6688 kg/cm2.